Freeing Tammy: women, drugs and incarceration - Raphael, Jody (The women, poverty and violence trilogy, 2007)
Prologue -- Betrayal -- Trial -- County jail -- Prison -- Numbing -- Minimum security -- Terrence alone -- The basement -- Forgetting -- Out of the basement -- Epilogue : back to county